Réponses

2013-12-22T23:50:16+01:00
Bonsoir

A = 49c² - 28c + 4
A = (7c - 2)²

B = (-3c + 2) (1- 2c) + (1-2c) (11c + 4)
B = (1 - 2c)[(-3c + 2) + (11c + 4)]
B = (1 - 2c)(-3c + 2 + 11c + 4)
B = (1 - 2c)(8c + 6)
B = 2(1 - 2c)(4c + 3)

C= (6c - 3)² - (3- 8c)²
C = [(6c - 3) + (3 - 8c)][(6c - 3) - (3 - 8c)]
C = (6c - 3 + 3 - 8c)(6c - 3 - 3 + 8c)
C = -2c(14c - 6)
C = -4c(7c - 3)
2013-12-23T00:13:20+01:00
1)A= 49c² - 28c + 4
A= 7²c² - 2*2*7*c +2²
A=(7c-2)²
2)B= (-3c + 2) (1- 2c) + (1-2c) (11c + 4)
B= (1-2c) (-3c+2+11c+4)
B= (1-2c) (8c+6)
3)C= (6c - 3)² - (3- 8c)²
C=36c²-36x + 9 - 9 + 48 c - 64 c²
C= -28c² +12c
C= 4c ( 3 - 7c)